Reação tecidual induzida pelos fios de quitosana e náilon em ratas (Rattus norvegicus) - Godeiro, José Renato Gurgel (Universidade Federal Rural do Semi-Árido, 2013)
Chitosan is a natural biopolymer that has large portfolio of structural applications with potential mechanical modifications to generate new properties, functions and specially applications in the biomedical field. This work evaluates the induced tissue reaction between chitosan and nylon sutures used on the skin and subcutaneously, after the 7th, 14th and 28th post-operative day. It was also observed the ability to remove the suture by degradation after application of the suture removal spray QiGel®. Thirty five rats were distributed in 2 groups, namely G1 (chitosan), with 20 rats, and G2 (nylon), with 15 ratsin 3 periods of observation. The G1 group had 5 extra rats for the removal test with the spray. The following evaluations were performed: clinical, macroscopic, tension force and histology. The results led us to conclude that the chitosan based sutures showed qualities contribute concerning removal with the Suture Removal QiGel® when compared with manual removal. The tension force evaluation showed that nylon is stronger than chitosan; however there was no difference on the sutured skin in the observed periods. The skin histology showed no difference on the quantification of fibroblast and collagen in both groups in the different observation periods
Induced tissue reaction between chitosan and nylon based sutures in rats (Rattusnorvegicus)
Keywords: Wealing; Wire chitosan; Tensiometry; Cicatrização; Fio de quitosana; Tensiometria; CIENCIAS AGRARIAS::MEDICINA VETERINARIA